2021
DOI: 10.1111/jcpp.13395
|View full text |Cite
|
Sign up to set email alerts
|

Examining the bidirectional association between emotion recognition and social autistic traits using observational and genetic analyses

Abstract: Background: There is mixed evidence for an association between autism spectrum disorder (ASD) and emotion recognition deficits. We sought to assess the bidirectionality of this association using phenotypic and genetic data in a large community sample. Methods: Analyses were conducted in three stages. First, we examined the bidirectional association between social autistic traits at age 8 years and emotion recognition task (ERT) responses at age 24 years (Study 1; N = 3,562); and between Diagnostic Analysis of … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 48 publications
(79 reference statements)
0
10
0
Order By: Relevance
“…These results strongly support the use of a consecutive point strategy as suggested by Clements et al . [32, 37]. We found that the original two-consecutive point strategy is insufficient for reducing the false positive rate with a more realistic null dataset.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…These results strongly support the use of a consecutive point strategy as suggested by Clements et al . [32, 37]. We found that the original two-consecutive point strategy is insufficient for reducing the false positive rate with a more realistic null dataset.…”
Section: Discussionmentioning
confidence: 94%
“…An adaptation of the methodology was included in [33] using an indicator function which depends on the time-series trend of each EWS. In this research, taking the negation of EWSs which are expected to decline prior to the tipping point was found to result in a more robust method than taking the positive summation of all EWSs [33, 37]. The trend of an EWS can depend on the type of data used [3] and hence it is important to first analyse each complex system analytically to determine the trend of each EWS, before applying the indicator adaption.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Emotion recognition was measured using the Diagnostic Assessment of Non-Verbal Accuracy (Nowicki & Duke, 1994) at mean age 8 years 8 months. We used the total number of facial emotions incorrectly identified (Reed et al, 2021). For bullying victimisation, we used the summed score of bullying behaviours (Table S3) reported by participants at mean age 12 years 10 months on the Bullying and Friendship Emotion dysregulation, disordered eating, and self-harm 8 Interview Schedule (Wolke, Woods, Stanford, & Schulz, 2001).…”
Section: Mediatorsmentioning
confidence: 99%
“…For example, poorer emotion recognition has been found in individuals with depression (Dalili et al, 2015; Demenescu et al, 2010), and this may be a causal factor in the maintenance of depressive symptoms (Warren et al, 2015). Similarly, autistic individuals or those scoring higher on autistic trait measures tend to have lower accuracy for global emotion recognition (Law Smith et al, 2010; Lozier et al, 2014; Reed et al, 2021). This may have implications for social development and interpersonal skills over time (Uljarevic & Hamilton, 2013).…”
Section: Introductionmentioning
confidence: 99%